Conocemos nuestros espacios naturales y sociales de mi localidad - Carlos Villegas, Celestina Santos (2019)
This research has the title We know our natural and social geographical spaces of my locality; which is designed for the fourth grade of Primary Education. In the introduction, the performance planning to evaluate the learning evidence and the assessment instrument to be used is in class planning Likewise, the didactic sequence of the social personnel area allows students to develop competencies and capacities through activities carried out such as elaborating schemes, describing, exchanging ideas, and thus building new knowledge, depending on their purposes. In the second chapter is the foundation of the area of social personnel, considering the profile of the graduation that the student must reach when completing the Regular Basic Education. In the third chapter it is dedicated to pedagogical support, referring to the psychopedagogical principles teaching processes of the area, as well as the techniques, means and materials, methodological process and evaluation instruments.